Pyridine derivatives complexes of Co(II) and Ni(II) 3-bromobenzoates: Crystal structure, in silico anti-SARS-CoV-2 potential, serum albumin binding properties and cytotoxicity - ÖZDEMİR, MÜCAHİT; YALÇIN, BAHATTİN (My University, 2023)
© 2023 John Wiley & Sons, Ltd.Two mononuclear [Co(3-BrBA)2(NA)2(H2O)2] (1) and [Ni(3-BrBA)2(3-CNPY)2(H2O)2] (2) (3-BrBA = 3-bromobenzoate, NA = pyridine-3-carboxylic acid, and 3-CNPy = 3-cyanopyridine) were synthesized and characterized by single crystal X-ray diffraction, elemental analysis, and FT-IR spectroscopy. In both complexes, the metal atom is coordinated by two oxygen atoms of two carboxylate anions, two nitrogen atoms of two pyridine rings, and two oxygen atoms of two water molecules in the distorted octahedral environment. Intermolecular interactions were examined with the help of the 3D Hirshfeld surfaces and 2D fingerprint plots. With the help of density functional theory (DFT) studies, besides verifying the experimentally obtained structural properties, the electronic energies, polarizability, dipole moments, ionization potentials, electron affinities, electronegativity, chemical hardness, global softness, electrophilic indexes, HOMO-LUMO orbitals, and band gaps were also calculated. In vitro cytotoxic activity of the complexes on primary peripheral blood mononuclear cells were evaluated using the MTT assay. Fluorescence quenching techniques and molecular docking studies were used to investigate the interaction between bovine serum albumin (BSA) and the complexes. The molecular docking study has been used to explain the interaction of complexes with spike proteins of beta variant (B.1.351), gamma variant (P.1), delta variant (B.1.617.2), kappa variant (B.1.617.1), and omicron variant (B.1.1.529) of coronavirus. Additionally, the pharmacokinetic and toxicological properties of the complexes have been computed using the SwissADME and ProTox-II online databases, respectively.
Keywords: Kimya; İnorganik Kimya; Temel Bilimler; Chemistry; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; Genel Kimya; Fizik Bilimleri; İnorganik kimya; General Chemistry; Physical Sciences; ADMET; arylcarboxylate; BSA; molecular docking; SARS CoV-2